Physico-chemical properties of Kaolin-organic acid - Yeo, S.W.; Ling, Felix Ngee Leh; Low, V. S.; Toh, K. L. (EDP Sciences, 2017)
Soil with more than 20% of organic content is classified as organic soil in Malaysia. Contents of organic soil consist of different types of organic and inorganic matter. Each type of organic matter has its own characteristic and its effect on the properties of the soil is different. Hence, a good understanding on the effect of specific organic and inorganic matter on the physico-chemical characteristic of organic soils can serve as a guide for predicting the properties of organic soils. The main objective is to unveil the effect of organic acid on the physico-chemical properties of soil. Artificial organic soil (kaolin mixed with organic acid) was utilized in order to minimize the geochemical variability of studied soil. The organic acid which consists of humic acid and fulvic acid was extracted from highly humificated plant–based compost. The effect of organic acid on the physico-chemical properties of soil was determined by varying the concentration of organic acid. The specific gravity, Atterberg limits, pH, bulk chemical composition and the functional group of kaolin-organic acid were determined. It was found that the plasticity index, specific gravity and pH value were decreased with lowered concentration of organic acid. However, the liquid limits and plastic limits were found to be increased with the concentration decrement of organic acid. The analysis of XRF on the bulk chemical composition and analysis of FTIR spectra on the functional group of artificial organic soils with different concentration have confirmed little geochemical variability between samples.